“Talk” an AI-Powered Speaking Partner Application - Dimas Vega Rizqyqa Putra Budiyono (STKIP AL HIKMAH SURABAYA, 2022)
With the advancement of technology, there are currently numerous tools and applications that are designed to facilitate students in improving their English speaking skills (Chun et al., 2016). One of these tools is called TALK. TALK is an online platform which is designed to help users improve their spoken English skills. It utilizes advanced speech recognition technology to provide users with feedback on their pronunciation, intonation, and overall spoken language proficiency.